Trust, Security and Privacy for Big Data - Alazab, Mamoun, 1980-; Gupta, Maanak, 1989- (CRC Press, Taylor & Francis Group, 2022)
"Data has revolutionized the current digital ecosystem. The readily available large datasets foster AI and machine learning automated solutions. However, the data format and its collection from various sources not only introduce unprecedented challenges to different domains including IoT, manufacturing, smart cars, power grids etc, but at the same time highlights the security and privacy issues in this age of big data. The humongous scale of extraordinary scale, security and privacy in big data faces many challenges, such as generative adversary networks, efficient encryption and decryption algorithms, encrypted information retrieval, attribute-based encryption, attacks on availability, and reliability. The purpose of this book is to offer a timely venue for researchers and industry partners in communications and networking domains to present and discuss their latest results in security and privacy related work of big data"--